A construção teórica da Diplomática: em busca de uma sistematização de seus marcos teóricos como subsídio aos estudos arquivísticos - Tognoli, Natália Bolfarini [UNESP] (2013)
Diplomatics offers a methodological approach to Information Science providing subsidies for documentary analysis in Archival Science. Its origin dates back to the seventeenth century, when in 1681, Mabillon published the work De re Diplomatica libri VI enunciating for the first time, the elements for document criticism. After Mabillon, other works were published in France, Austria, Germany and Italy contributing to the consolidation of the discipline within the so called “documentary sciences”, admitting concepts and methods for the criticism of medieval documents. However, despite the long list of works, the literature still lacks a systematization of the ideas of classical authors that make up the discipline, more specifically, how they interact and work to its constitution. This systematization is important once authors as Bautier (1962), Duranti (1995) and Heredia (1991) identified in those works, the earliest theoretical and practical manifestations for archival organization. Thus, this dissertation performs a theoretical reunion of Diplomatics from the study of its major works published between the seventeenth and twentieth centuries, aiming to identify the role they play in the construction of both disciplines, systematizing the ideas of the more expressive frameworks of the area in order to build a ideal type of diplomatics method. To do so, it was carried out an exploratory, theoretical and documentary study in the works of Diplomatics identifying the nature, object and purpose of discipline, so it could be built a cartography of authors who integrate the epistemological constitution of the area, as well as an ideal type of diplomatic method, able to deal with old and contemporary documents